THE EFFECT OF PHYSICAL EXERCISES ON THE HUMAN BODY AND THE ATTITUDE OF OUR YOUTH TO SPORTS CULTURE - To‘xtayev Juma Jo‘rayevich. (Proximus Journal Publishing, 2024)
This article talks about the effect of physical exercises on the human body and the attitude of young people in our country to the sports culture, as well as the effective use of sitas. Scientists' definitions of physical training are explained to the human body by the development of muscles and physical exercises
Keywords: physical training; physical exercises; muscles